Late diagnosis of heel sarcoma - Ponce Villar, Úrsula; Peiró Monzó, Fabián; Seguí Gregori, Jesús (Cirugía del Uruguay, 2020)
39-year-old woman, consulted for heel pain for a year, with anodyne X-ray. At 5 months, she presented an abscessed tumor in the heel (Fig. 1), and drainage and biopsy of the tumor was performed, which reported high-grade spindle cell sarcoma. An MRI study was completed, which described a 5-cm excretory tumor contacting the calcaneus and plantar fascia (Fig. 2: yellow arrows). It was pending to start chemotherapy. After a month, she presented with cough and hemoptysis, and the chest tomography revealed bilateral pulmonary metastases with a large tumor in the right upper lobe (Fig. 3: yellow arrows). At 15 days, he presented an acute abdomen, and emergency surgery was found to find jejunal perforation due to a tumor implant with peritoneal carcinomatosis and multiple liver metastases. A segmental resection of the jejunum with anastomosis was performed, and she was discharged and died after a month due to the evolution of the disease. Sarcomas present a rapid progression with development of metastases. The early diagnosis of these tumors is vital to improve the prognosis.